Plant Secondary Metabolites, Their Classification and Biological Roles: A Review - Enas Naji; Hiba Fouad Abdulfatah; Khader AlZawi (مجلة جامعة الانبار للعلوم الصرفة)
Metabolism represents the primary and essential biological phenomenon occurring within the living cell, encompassing the synthesis of crucial biomolecules and their subsequent breakdown to liberate the requisite energy for diverse cellular functions. Two distinct forms of metabolism exist: primary and secondary, the primary one, facilitating the production of fundamental organic substances to support growth, reproduction, and other biological processes, including proteins, carbohydrates, lipids, and nucleic acids. Plants constitute an indispensable reservoir of chemical compounds possessing diverse biological attributes that can be exploited by humans for their benefit. These substances primarily emerge through chemical transformations of secondary metabolism includes terpenes, alkaloids, phenolic compounds, saponines, steroids each group possesses unique traits and attributes that set it apart from other groups, and each of these categories fulfills crucial and indispensable functions within the majority of living cells.. These secondary metabolites are synthesized in minute amounts that are sufficient to fulfill specific plant needs in response to particular environmental factors. These compounds possess unique properties that enable them to play important biological roles not only in the life of plants, but also in the life of other living organisms, including humans.